Bioassay-guided isolation of cytotoxic flavonoids from aerial parts of Coronopus didymus. (24th December 2016) - Noreen, Hafiza; Farman, Muhammad; McCullagh, James S.O.
Abstract: Ethnopharmacological relevance: Coronopus didymus Linn. (Brassicaceae) is a medicinal plant used traditionally as antipyretic, expectorant, to purify blood and for alleviating symptoms of pain, inflammations, malaria, wounds and cancer. Aim of the study: The present study was designed to isolate and identify the cytotoxic compounds responsible for anticancer activity from this traditionally useful medicinal plant. Materials and methods: Bioassay-guided fractionation of the ethanolic extract of aerial parts of C. didymus allowed the isolation of compounds responsible for anticancer activity. Their structures were elucidated by UV Spectroscopy (with shift reagents), ESI-MS and NMR spectral data. Preliminary anticancer activity of ethanolic extract, different fractions and isolated compounds was assessed through MTT in vitro cytotoxicity assay in a dose dependent manner against human cancer cell lines (HeLa and LN18) and normal 293T cells. Results: Three flavonoids namely 5, 7, 4′-trihydroxy-3′-methoxyflavone-4′- O - β -D -glucoside (1 ), 5, 7, 4′-trihydroxy-3′-methoxyflavone-4′- O -(6''-acetyl)- β -D -glucoside (2 ) and 5, 7, 4′-trihydroxy-3′-methoxy flavone (3 ), were isolated from aerial parts. Compound1 was identified for the first time from the genus Coronopus . All the compounds1 –3 showed promising activity against HeLa cells with IC50 values of 43.50, 0.63 and 3.67 µM , respectively. Significant result was also obtained with compound3 against LN18 cells with IC50 value of 46.63 µM . Conclusion: The cytotoxic activity of the crude extract and fractions which may largely be due to its major isolated constituents, flavonoids1 –3, against both HeLa and LN18 cells provides a scientific basis for the ethnopharmacological use of C. didymus as anticancer agent. Graphical abstract: